Serum Insulin-Like Growth Factor-1 in Parkinson's Disease; Study of Cerebrospinal Fluid Biomarkers and White Matter Microstructure - Ghazi Sherbaf, Farzaneh; Mohajer, Bahram; Ashraf-Ganjouei, Amir; Mojtahed Zadeh, Mahtab; Javinani, Ali; Sanjari Moghaddam, Hossein; Shirin Shandiz, Mehdi; Aarabi, Mohammad Hadi (Frontiers in Endocrinology, 2018)
Background: Growing evidence shows that impaired signaling of Insulin-like Growth Factor-1 (IGF-1) is associated with neurodegenerative disorders such as Parkinson's Disease (PD). However, there is still controversy regarding its proinflammatory or neuroprotective function. In this study, we aimed to discover the relation between serum IGF-1 levels in drug-naïve early PD patients and cerebrospinal fluid (CSF) biomarkers as well as microstructural changes in white matter tracts, trying to elucidate the contribution of IGF-1 in PD. Methods: Association between quartiles of serum IGF-1 levels and CSF biomarkers (α-synuclein, dopamine, amyloid-β1-42, total tau, and phosphorylated tau) were investigated using adjusted regression models in 404 drug-naïve early PD patients with only mild motor manifestations and 188 age and sex-matched healthy controls (HC) enrolled in the Parkinson’s Progression Markers Initiative (PPMI). Through region of interest analysis and connectometry approach, we tracked the white matter microstructural integrity and diffusivity patterns using diffusion MRI (dMRI) of a subgroup of study participants with available dMRI data with acceptable quality to investigate the association between subcomponents of neural pathways with serum IGF-1 levels. Result: PD patients had not significantly higher levels of IGF-1 compared to HC (Mean difference: 3.60, P=0.44). However, after adjustment for possible confounders and correction for False Discovery Rate (FDR), IGF-1 was negatively correlated with CSF α-synuclein, total and phosphorylated tau levels only in PD subjects. The connectometry analysis proved significant (FDR corrected P-value = 0.013) negative correlation between the serum IGF-1 continuous levels of patients with PD and the connectivity, and not integrity in following fibers while controlling for age, sex, body mass index (BMI), depressive symptoms, education years, cognitive status and disease duration: middle cerebellar peduncle, cingulum, genu and splenium of the corpus callosum. No significant association was found between brain white matter connectivity or CSF markers of healthy controls and levels of IGF-1. Conclusion: The disruption of connectivity in specific white matter structures, mainly involved in cognitive and motor deterioration, with higher serum IGF-1 levels, might propose IGF-1 as a potential associate of worse outcome in response to greater pathological insults in terms of higher burden of α-synucleinopathy and tauopathy.